PRODUKSI MANISAN RAMBUTAN KERING DENGANVARIASI KONSENTRASI LARUTAN KAPUR DAN KARAKTERISTIK PENGERINGAN - Sri Hastuti; Yuli Dwi Kurnianti; Muhammad Fakhry (AGROINTEK, 2013)
Rambutan susceptible to damage due to respiration and transpiration processes thatcause huge losses to farmers and traders , even the price of rambutan to be low due to the highproduction and efficient distribution of marketing . One alternative to reduce the level ofdamage to the fruit rambutan is to make candied dried rambutan . The purpose of this study wasto determine the effect of drying characteristics and concentration of lime solution to the watercontent , texture and vitamin C in the making candied dried rambutan . The method used RAK (completely randomized design ) with factorial . The results of this study indicate that the use oflime solution concentrations result in increased water content but had no effect on the levels ofvitamin C , hardness and resilience . While the differences in drying characteristics and theirinteraction did not affect the increase in water content , vitamin C content, hardness andresilience.